2003
DOI: 10.1093/glycob/cwh018
|View full text |Cite
|
Sign up to set email alerts
|

Human galectin-1 recognition of poly-N-acetyllactosamine and chimeric polysaccharides

Abstract: Human galectin-1 is a dimeric carbohydrate binding protein (Gal-1) (subunit 14.6 kDa) widely expressed by many cells but whose carbohydrate binding specificity is not well understood. Because of conflicting evidence regarding the ability of human Gal-1 to recognize N-acetyllactosamine (LN, Galbeta4GlcNAc) and poly-N-acetyllactosamine sequences (PL, [-3Galbeta4GlcNAcbeta1-]n), we synthesized a number of neoglycoproteins containing galactose, N-acetylgalactosamine, fucose, LN, PL, and chimeric polysaccharides co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
95
1
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 71 publications
10
95
1
7
Order By: Relevance
“…1c) and the a3 sialyl-N-Acetyllactosamine (a3 SiaLacNAc) belonging to group (ii) (Fig. 1c), for which a relative decrease and increase in GAL1 binding, respectively, are observed in the presence of the l5-UR domain (binding of these two glycans to GAL1 has been demonstrated previously 31,32 ). In our experimental conditions, the dissociation constant (K D ) of GAL1/LNnT interaction obtained is 51±6 mM, whereas when GAL1 is bound to the l5-UR domain, the K D increases to 130±10 mM, that is, a 2.5-fold decrease in binding affinity of LNnT for GAL1 in the presence of l5-UR (Supplementary Table 1).…”
Section: Gal1 Carbohydrate-binding Specificity When Bound To K5-ursupporting
confidence: 51%
“…1c) and the a3 sialyl-N-Acetyllactosamine (a3 SiaLacNAc) belonging to group (ii) (Fig. 1c), for which a relative decrease and increase in GAL1 binding, respectively, are observed in the presence of the l5-UR domain (binding of these two glycans to GAL1 has been demonstrated previously 31,32 ). In our experimental conditions, the dissociation constant (K D ) of GAL1/LNnT interaction obtained is 51±6 mM, whereas when GAL1 is bound to the l5-UR domain, the K D increases to 130±10 mM, that is, a 2.5-fold decrease in binding affinity of LNnT for GAL1 in the presence of l5-UR (Supplementary Table 1).…”
Section: Gal1 Carbohydrate-binding Specificity When Bound To K5-ursupporting
confidence: 51%
“…By contrast, it was reported that bovine dGal-1 binds with relatively high affinity to immobilized extended (neo)glycolipids in TLC overlay and microwell binding assays, whereas binding to nonextended structures was not detected (42). Similarly, human dGal-1 is able to recognize immobilized neoglycoproteins containing PLs with higher affinity compared with immobilized neoglycoproteins with non-extended oligosaccharides in a solidphase assay (43). The apparent discordance of these results may now be resolved since we have shown that they reflect the differing affinity of Gal-1 for ligands free in solution or immobilized on surfaces.…”
Section: Galectin-1 Binding To Terminal N-acetyllactosamine Unitsmentioning
confidence: 88%
“…In contrast to these studies, recent data have suggested that dGal-1 may not recognize PL structures with higher affinity compared with its recognition of short non-extended structures (44,45). Interestingly, dGal-1 has been suggested to bind primarily to nonreducing terminal LN residues rather than to mid-chain LN residues within a PL chain (42,43,46).…”
mentioning
confidence: 87%
See 2 more Smart Citations